Freedomland - Price, Richard, 1949- (Broadway Books, 1998)
When Brenda Martin claims her car was stolen with her son in the backseat, the chilling accusation sparks an intense investigation led by Detective Lorenzo Council. The frenzy to find her son escalates into an explosive nightmare of suspicion and accusation, and the search for the truth leads to riveting action, disturbing revelations, and a shocking ending.